Translanguaging in South African Primary Mathematics Education: A Semi-Systematic Review of Pedagogical Opportunities for Multilingual Learners - Erasmos Charamba; Shalom Nokuthula Ndhlovana (JOLLT Journal of Languages and Language Teaching, 2026)
South African primary mathematics classrooms remain linguistically complex due to the mismatch between learners’ home languages and the dominant language of instruction. This mismatch continues to contribute to poor learner participation, conceptual misunderstanding, and low mathematics achievement. This semi-systematic review explores how translanguaging can be harnessed as a pedagogical resource in multilingual South African primary mathematics classrooms. Eight peer-reviewed studies published between 2020 and 2023 were selected following a structured search and screening process using predefined inclusion and exclusion criteria. Studies were retrieved from Google Scholar, Scopus, and ResearchGate and analysed thematically using Braun and Clarke’s six-phase framework. Findings reveal that translanguaging enhances classroom communication, supports conceptual meaning-making, strengthens learner participation, and improves mathematical proficiency by allowing learners to draw on their full linguistic repertoires. The review highlights the need for language-responsive pedagogies, teacher professional development, and multilingual classroom policies that promote equitable mathematics learning in South African schools.